2005
DOI: 10.1096/fj.04-2370com
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate blocks a non‐Smad TGF‐β pathway and reduces renal fibrogenesis in vivo

Abstract: Transforming growth factor-beta (TGF-beta) is the single most important cytokine promoting renal fibrogenesis. p21-activated kinase-2 (PAK2) and activation of abelson nonreceptor tyrosine kinase (c-abl) have been shown recently to be smad-independent, fibroblast-specific targets downstream of the activated TGF-beta receptor. In the current study we show that in cultured NRK49F-renal fibroblasts (but not in tubular or mesangial cells) TGF-beta similarly activates PAK2 as well as c-abl and induces cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
242
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 351 publications
(258 citation statements)
references
References 38 publications
(46 reference statements)
15
242
1
Order By: Relevance
“…Indeed, consistent with the data presented herein, imatinib mesylate has been shown to reduce the accumulation of ECM proteins in a model of pulmonary fibrosis. In addition, it reduced renal ECM accumulation in a model of unilateral obstructive nephropathy (11)(12)(13).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, consistent with the data presented herein, imatinib mesylate has been shown to reduce the accumulation of ECM proteins in a model of pulmonary fibrosis. In addition, it reduced renal ECM accumulation in a model of unilateral obstructive nephropathy (11)(12)(13).…”
Section: Discussionmentioning
confidence: 95%
“…Imatinib mesylate is a small-molecule tyrosine kinase inhibitor that binds to the ATP-binding pocket of c-Abl and efficiently blocks its tyrosine kinase activity. Notably, c-Abl has recently been identified as an important downstream molecule in TGF␤ signaling (11)(12)(13). Using mouse embryonic fibroblasts deficient in c-Abl, Daniels et al demonstrated that c-Abl is crucial for the induction of ECM proteins by TGF␤ and that inhibition of c-Abl by imatinib mesylate reduced the synthesis of ECM components in vitro and in vivo in a lung fibrosis model (11).…”
mentioning
confidence: 99%
“…In contrast, the structurally divergent Smad6 and Smad7 inhibit TGF-β signaling (inhibitory Smads). Recently, it has become increasingly apparent that TGF-β not only activates Smads, but also signals through Smad-independent pathways [321] that may involve c-Abl [322], p21-activated kinase-2 (PAK2) [323], TGF-β Activated Kinase (TAK)-1 [324], and p38 MAPK [325].…”
Section: Tgf-β Signaling Pathways In Cardiac Injurymentioning
confidence: 99%
“…With respect to fibrosis, the nonreceptor tyrosine kinase c-Abl is of special interest, because of the potent antifibrotic effects of the pharmacologic inhibitor of c-Abl, imatinib mesylate. Imatinib mesylate has been shown to inhibit profibrotic effects of TGF␤ in cultured cells, including SSc fibroblasts (5), and to prevent lung and kidney fibrosis in experimental mouse models (6,7). TGF␤ activation of c-Abl occurs through phosphatidylinositol 3-kinase and p21-activated kinase 2 and is independent of the Smad2/3 pathway (8).…”
mentioning
confidence: 99%